Cechy stabilnego systemu finansowego - Ostalecka, Agnieszka (The Indicators of Financial System Stability, 2005)
The article is a trial of presenting the features of financial system which promote its stability. These features have been presented in two groups: micro and macroeconomic features. To the macroeconomic indicators of financial system stability it has been subsumed cohesion the instruments of monetary and fiscal policy and properly prepared and sequentially introduced financial liberalisation. However, the microeconomic features of financial system stability are: well-defined legal framework and credibility and transparency of financial institution functioning, high quality of management and corporate governance, effective control and supervision on financial institution, market discipline and well-defined safety net.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 51-61